2005
DOI: 10.5194/hessd-2-2625-2005
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of two model approaches in the Zambezi river basin with regard to model reliability and identifiability

Abstract: Abstract. Variations of water stocks in the upper Zambezi river basin have been determined by 2 different hydrological modelling approaches. The purpose was to provide preliminary terrestrial storage estimates in the upper Zambezi for comparison with estimates derived from the Gravity Recovery And Climate Experiment (GRACE). The first modelling approach is GIS-based, distributed and conceptual (STREAM). The second approach uses lumped elementary watersheds identified and modelled conceptually (LEW). The STREAM… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 10 publications
1
19
0
1
Order By: Relevance
“…In contrast, low BWI values (less than 1) contain a high confidence that the flow will be near the base flow. These results compared favorably to model prediction for the Zambezi presented by Winsemius et al (2006), whose predictions were based on a more complex model. As a result, the BWI can be a quantitative indicator for periods and frequencies of flow associated with limited water -of particular relevance to obligations and commitments agreed upon in international water treaties.…”
Section: Monitoring River Flowsupporting
confidence: 53%
“…In contrast, low BWI values (less than 1) contain a high confidence that the flow will be near the base flow. These results compared favorably to model prediction for the Zambezi presented by Winsemius et al (2006), whose predictions were based on a more complex model. As a result, the BWI can be a quantitative indicator for periods and frequencies of flow associated with limited water -of particular relevance to obligations and commitments agreed upon in international water treaties.…”
Section: Monitoring River Flowsupporting
confidence: 53%
“…The water balance is calculated for each grid-cell using a direct runoff, soil water and groundwater component (see Appendix A). The STREAM model has been successfully applied in various forms for climate and hydrology studies in a number of river basins with similar size and characteristics as the Krishna river basin (Van Deursen and Kwadijk, 1994;Aerts et al, 1999;Aerts et al, 2000;Middelkoop et al, 2001;Winsemius et al, 2006). These studies have confirmed that a monthly time step is sufficient for detecting decadal, inter-annual and seasonal changes in the hydrological cycle, such as those caused by water consumption and climatic change.…”
Section: The Stream Modelmentioning
confidence: 57%
“…Compared with past attempts to model discharges in key locations of the Zambezi basin (Vorosmarty et al 1991;Harrison & Whittington 2002;Winsemius et al 2006a;Meier et al 2011), the results can be considered as acceptable for applying the model to simulate development scenarios, taking into account the fact that the scenarios comparison will be based on relative values. The present work constitutes a significant contribution in terms of reliability and error assessment as it implemented a thorough validation procedure and used a hydrological model tailored to meet some of the specificities of the Zambezi River basin.…”
Section: Discussionmentioning
confidence: 99%
“…In another modeling attempt, the Spatial Tools for River basin Environmental Analysis and Management 2 T. Cohen Liechti et al (Aerts et al 1999) and a Lumped Elementary Watershed model were calibrated on the same sub-basin over the period 1960-1972 at a monthly time step (Winsemius et al 2006a). The NS coefficient was about 0.8.…”
Section: Introductionmentioning
confidence: 99%